EFISIENSI PERAWATAN KULIT LUAR BANGUNAN DITINJAU DARI FASILITAS DAN TINDAKAN PERAWATAN - Rustandi, Melisa (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Parahyangan, 2009)
Abstract Vertical plan housing is an effective choice for saving energy building concept. This vertical house could shelter many spaces and anticipating the problem of limited land, especially at the big cities. One of the problems in vertical housing, especially in high rise building is